Liposuction in body-shaping treatment for Kobberling-Dunnigan syndrome - Colombo,André Ratto (2011)
INTRODUCTION: Kobberling-Dunnigan syndrome is characterized by a series of alterations in metabolism and body fat distribution. Body dysmorphism and the Cushingoid appearance may have negative social and psychological impacts on the patient, including difficulty with social adaptation. In such cases, liposuction is used with the aim of improving body contour, with consequent improvements in self-esteem. The results are long lasting when body weight is maintained. CASE REPORT: Liposuction of the back, abdomen, and cervical regions in a woman with Kobberling-Dunnigan syndrome led to significant improvement in her body shape, and the results were maintained nine months postoperatively.